Nutritional risk factors for SARS-CoV-2 infection: prospective study from the NutriNet-Santé cohort. (20th October 2021) - Deschasaux-Tanguy, M; Bourhis, L; Druesne-Pecollo, N; Esseddik, Y; Galan, P; Hercberg, S; de Lamballerie, X; Carrat, F; Touvier, M
Abstract: Background: Many hypotheses were raised regarding a role of nutrition in COVID-19 (susceptibility to infection, disease severity) based on the importance of macronutrients, vitamins or minerals for a proper functioning of the immune system. Our objective was to study the associations between dietary intakes and the seroprevalence SARS-CoV-2 infection in a large population-based sample. Methods: Our analyses included 7766 adults from the French NutriNet-Santé cohort who provided at least 6 valid 24h dietary records in the two years preceding the start of the COVID-19 pandemic in France (February 2020). An ELISA assay was used to detect anti-SARS-CoV-2 antibodies: 311 participants were positive and 7455, negative. Associations between dietary intakes and the seroprevalence of anti-SARS-CoV-2 antibodies were investigated using multi-adjusted logistic regressions. Results: A lower seroprevalence of SARS-CoV-2 infection was associated to higher intakes of vitamin B9 (HR = 0.84 (0.72-0.98)), vitamin C (HR = 0.85 (0.75-0.97)), vitamin K (HR = 0.86 (0.74-0.99)), dietary fibres (HR = 0.84 (0.72-0.97)), and fruit and vegetables (HR = 0.84 (0.74-0.97)). Higher intakes of calcium (HR = 1.17 (1.01-1.35)) and dairy products (HR = 1.19 (1.06-1.33)) associated to a higher seroprevalence of SARS-CoV-2 infection. No association was observed with other food groups or nutrients or with the overall diet. Conclusions: Based on exhaustive seroprevalence data in a large population-based sample, our results suggested that higher intakes of vitamin C, folates, vitamin K, dietary fibres and fruit and vegetables were associated with a lower susceptibility to SARS-CoV-2 infection. Key messages: Higher intakes of vitamin C, folates, vitamin K, dietary fibres and fruit and vegetables were associated to a lower susceptibility to SARS-CoV-2 infection, assessed with exhaustive seroprevalence data. Beyond its established role in the prevention of non-communicable diseases, nutrition could also contribute to prevent some infectious diseases such as COVID-19.